Gender Parity and Democracy: A Perspective from the Municipal Councils - León Loza, Mateo Javier (2023)
Gender parity is considered as the most important legal mechanism in defense of equitable political participation and representation between men and women for the constitution of public and decision-making organizations in an equitable manner. This article focuses on the analysis of the incursion and impact of gender parity in Ecuadorian legislation and its repercussion on the structuring of cantonal legislative organizations. Under a qualitative methodology on analysis and documentary review, the inductive method is adopted, to address the comprehensive foundation that supports the precept of parity, such as political participation and representation, formal and material equality and non-discrimination, equity and democracy. Underscoring that the legal regulations defend the exercise of the electoral system under the principle of gender parity, the development of innovative and different electoral processes with parity criteria, equity, alternability and sequentiality that guarantee inclusion is recommended.The municipal councils are cantonal legislative organizations that need to be constituted with men and women members, who represent the population, to allow them to collectively and collaboratively address the needs and interests of society. Although this aspiration is far from reality, as despite the legal requirement for parity, the current scenarios are causing a female underrepresentation and a democratic weakening.